Development of Polymeric Nanoparticles of Garcinia mangostana Xanthones in Eudragit RL100/RS100 for Anti-Colon Cancer Drug Delivery - Abdalrahim F. A., Aisha; Abdulmajid, Amin Malik Shah; Ismail, Zhari; Alrokayan, Salman A.; Abu-Salah, Khalid M. (Hindawi Publishing Corporation, 2015)
Xanthones are a group of oxygenated heterocyclic compounds with anticancer properties, but poor aqueous solubility and low oral bioavailability hinder their therapeutic application. This study sought to prepare a xanthones extract (81%